Hepatocyte Transplantation (HTx) Corrects Selected Neurometabolic Abnormalities in Murine Intermediate Maple Syrup Urine Disease (iMSUD) - Skvorak, Kristen J. (2009)
Skvorak and coworkers [1] demonstrated the therapeutic efficacy of HTx in a murine model of iMSUD, confirming significant metabolic improvement and survival. To determine the effect of HTx on extrahepatic organs, we examined the metabolic effects of HTx in brain from iMSUD animals. Amino acid analysis revealed that HTx corrected increased ornithine, partially corrected depleted glutamine, and revealed a trend toward alloisoleucine correction. For amino acid and monoamine neurotransmitters, decreased GABA was partially corrected with HTx, while the L-histidine dipeptide of GABA, homocarnosine, was decreased in iMSUD mice and hypercorrected following HTx. Elevated branched chain amino acids (BCAA; leucine, isoleucine, valine) in MSUD can deplete brain tyrosine and tryptophan (the precursors of monoamine neurotransmitters dopamine (DA) and serotonin (5-hydroxytryptamine; 5-HT)) through competition via the large neutral amino acid transporter. HTx corrected decreased DA levels and the DA metabolite, 3-methoxytyramine, and partially corrected the DA intermediate 3,4-dihydroxyphenylacetate (DOPAC) and 5-HT levels, despite normal tyrosine and tryptophan levels in iMSUD mouse brain. We further observed enhanced intracellular turnover of both DA and 5-HT in iMSUD mouse brain, both of which partially corrected with HTx. Our results suggest new pathomechanisms of neurotransmitter metabolism in this disorder and support the therapeutic relevance of HTx in iMSUD mice, while providing proof-of-principle that HTx has corrective potential in extrahepatic organs.